The implementation of online learning during COVID-19: An evaluation study on selected supervised schools - Reni Herawati; Aris Priyanto (Universitas Sarjanawiyata Tamansiswa, 2020)
This study is for evaluating the management of online learning during COVID-19 on selected supervised schools in Yogyakarta. This evaluation study used a descriptive quantitative approach with the CIPP model. One hundred forty-nine respondents were selected purposively from 7 (seven) schools in Yogyakarta, Indonesia. The study retrieved the data from online questionnaires, observation, documentation study, and interviews. The result revealed the empirical data: 1) the implementation of online learning was successful, 2) the main obstacles of online learning were the teacher readiness in conducting online learning and the problem of internet access, and 3) the remarkable advantages of online learning during COVID-19 were: the quick shift and innovation of learning method using online learning platforms among teachers, the improvement of teacher and student creativity.